Not all viruses cause disease: HERV-K(HML-2) in healthy human tissues - Srinivasachar Badarinarayan, Smitha; Sauter, Daniel (PLOS Biology, 2022)
Human endogenous retroviruses (HERVs) make up a significant part of our genomes. Their expression is frequently associated with disease, but this Primer explores the implications of a new study in PLOS Biology which found that HERV-K (HML-2) is expressed in more than 50 healthy tissues. Several of these viral DNA fossils have retained intact open reading frames and may encode functional proteins.